A systematic review into the incidence, severity and duration of antidepressant withdrawal effects: Are guidelines evidence-based?. (October 2019) - Davies, James; Read, John
Highlights: More than half (56%) of people who attempt to come off antidepressants experience withdrawal effects. Nearly half (46%) of people experiencing withdrawal effects describe them as severe. It is not uncommon for the withdrawal effects to last for several weeks or months. Current U.K. and U.S.A. Guidelines underestimate the severity and duration of antidepressant withdrawal, with significant clinical implications. Abstract: Introduction: The U.K.'s current National Institute for Health and Care Excellence and the American Psychiatric Association's depression guidelines state that withdrawal reactions from antidepressants are 'self-limiting' (i.e. typically resolving between 1 and 2 weeks). This systematic review assesses that claim. Methods: A systematic literature review was undertaken to ascertain the incidence, severity and duration of antidepressant withdrawal reactions. We identified 24 relevant studies, with diverse methodologies and sample sizes. Results: Withdrawal incidence rates from 14 studies ranged from 27% to 86% with a weighted average of 56%. Four large studies of severity produced a weighted average of 46% of those experiencing antidepressant withdrawal effects endorsing the most extreme severity rating on offer. Seven of the ten very diverse studies providing data on duration contradict the U.K. and U.S.A. withdrawal guidelines in that they found that a significant proportion of people who experience withdrawal do so for more than two weeks, and that it is not uncommon for people to experience withdrawal for several months. The findings of the only four studies calculating mean duration were, for quite heterogeneous populations, 5 days, 10 days, 43 days and 79 weeks. Conclusions: We recommend that U.K. and U.S.A. guidelines on antidepressant withdrawal be urgently updated as they are clearly at variance with the evidence on the incidence, severity and duration of antidepressant withdrawal, and are probably leading to the widespread misdiagnosing of withdrawal, the consequent lengthening of antidepressant use, much unnecessary antidepressant prescribing and higher rates of antidepressant prescriptions overall. We also recommend that prescribers fully inform patients about the possibility of withdrawal effects.